STUDI ISLAM DENGAN PENDEKATAN INTERDISIPLINER: URGENSI DAN APLIKASINYA - Hayatullah Hilmi Aziz; Imroatul Azizah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
Abstract: Islamic studies which are only normative in nature seem unable to answer the challenges of the times which are experiencing rapid development. Therefore, an interdisciplinary approach is needed which is expected to be a solution to unsatisfactory answers from monodisciplinary studies of Islam. This article uses descriptive analysis with a qualitative approach and is a type of library research. The result is an interdisciplinary approach that does not yet have a specific methodology and research steps. This happens because the interdisciplinary scope is so broad, that the interdisciplinary approach only completes the methodology and steps based on their respective fields of knowledge. However, based on the application carried out by experts, the method is to determine Islamic titles/problems, bring together two or three different knowledge clusters but still related to the topic of the problem, interact between scholars, study in depth, and provide conclusions. This method is able to produce new findings and answer community problems. The conclusion from the example, the interpretation of the seven layers of heaven does not contradict the scientific facts put forward by Edwin Huble. Edwin only explained that the sky is wide like the root of the word “sama>’ which means “high/broad”.